FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN: STUDI PADA PERUSAHAAN BARANG KONSUMEN NON-PRIMER - Chandra, Maria Shelyn; Ardana, I Cenik; Simina, Juni (Jurnal Paradigma Akuntansi, 2025)
The purpose of this study was to obtain empirical evidence about the effect of managerial ownership, institutional ownership, capital structure, profitability, and liquidity on firm value. The subjects of this study are Non-Primary Consumer Goods Sector Companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2021 period. The sample was selected using the purposive sampling method, and 9 companies were obtained with a total sample for 5 years (2017-2021) of 45 samples. The data was processed using Microsoft Excel 2019 and Eviews version 12 software. Hypothesis testing uses multiple regression models. The results showed that managerial ownership had a significant positive effect on firm value, but institutional ownership, capital structure, profitability and liquidity had no effect on firm value. The implication of this study is the need of firm management and institution role, high capital structure and profitability level, also liquidity level that meet the standard to achieve an optimal firm value.